Intergenerational Educational Mobility and Identity: a French-Argentine Comparative Study (European Journal of Social Science Education and Research, 2019)
This study forms part of the author’s longstanding research regarding social, educational and professional mobility observed in Argentina across three generations, associated with the factor of Education and with the greater flow of immigrants in the last century. This research encompasses various smaller studies. Here we mention one, a French-Argentine comparative study in which we worked with PhD s from different institutions and different social science PhD programs. Our objective was: a) to analyze what factors (quantitative) and what reasons (qualitative) positively and negatively impacted professional pathways (career mobility); b) to observe the level of educational mobility present in families with PhD s, taking the issue from different paradigms (reproductionist/interactionist): University of elites? University of the masses? The methodology was both quantitative and qualitative, using semi-structured surveys (which included open-ended statements so respondents could expand); the hierarchical evocation technique and interviews. Results: a) we observed the intergenerational educational mobility of PhD s (quantitative-descriptive level); b) we understood some of the “reasons” and “sense” that underlie said mobility and that have either acted as driving forces or have not acted as driving forces of social and cultural-educational promotion (qualitative level). c) We found similar levels of intergenerational educational mobility for PhD s in France and Argentina (graduates of various PhD programs). This result is interesting in the face of well-held myths of educational “hypo mobility” , intergenerational drops in mobility, stagnation, a lack of educational/cultural promotion under “plafond” effects, or a saturation of degree holders, above all in developed countries. From the point of view of identity, this high level of intergenerational educational mobility impacted national, institutional and micro individual identity; three planes in sustained interaction using the author’s theory: The Three Dimensional Spiral of Sense ((2015 a and b).